Temporal based knowledge management for university innovation product - Hussain, Imamuddeen
The Ministry of Education Malaysia has encouraged public universities to enhance the development of innovation products that can give competitiveness impact to universities at the international level. The priority is given to innovation products which include tangibleand intangible products, which can generate income for the university. Currently, most universities manage innovation products developed by researchers manually and without the use of any proper information management system. The information of the product is documented in the files based on explicit knowledge. Thus, this situation can lead to the problems in sorting and accessing the records as the record becomes larger over time. Therefore, a systematic knowledge management model for university innovation product is highly demanded. This research aims to develop a model which considers the storing and distribution process of three pillars in knowledge management by utilizing the temporal data approach. Two elements of time are embedded into the proposed model which is transaction date and valid date. The use of time elements and temporal operators produce a new schema to the knowledge transaction and retrieval based on past, present and future time. In addition, based on this proposed model a prototype has been developed and evaluated using the data from the Center for Research and Innovation Management (CRIM) , Universiti Sultan Zainal Abidin (UniSZA). The performance of the model is measured using questionnaire which is based on four attributes of usability metrics. The results show 89.5% of the respondents agreed with the efficiency of the model, 88.5% agreed with its effectiveness, 84.7% and 82.9% agreed with its accessibility and functionality respectively. The proposed model provides a platform for university to manage the innovation products effectively. Hence, it enhances the record tracing of innovation products and allows the stakeholders efficiently manage the records.